Effect of the season on the production and chemical properties of fish protein hydrolysates and high-quality oils obtained from gurnard (Trigla spp.) by-products. (1st March 2023) - Vázquez, José Antonio; Valcarcel, Jesus; Sapatinha, Maria; Bandarra, Narcisa M.; Mendes, Rogério; Pires, Carla
Abstract: Currently valorization of fish discards by-products is becoming fundamental for the sustainable management of fisheries and seafood transforming industries. Thus, we have studied the changes in the production and chemical properties of fish protein hydrolysates (FPH) and oils from by-products (heads (He) and skins + bones (SB)) of gurnard ( Trigla spp.) captured at different seasons. Hydrolyses were performed by Alcalase (2.5 mL/kg of by-product) at pH 8.60, 60.6 °C, 200 rpm, for 3 h. Seasonality effect was not significant in the majority of FPH properties, obtaining high digestion yields and excellent amino acid contents (more than 43% of essential amino acids per total amino acids in He). However, the maximum degree of hydrolysis for He were higher (24–26.5%) than observed for SB (19–23.6%). In the case of oil, concomitantly recovered to the production of hydrolysates, the yield of recovery was largest in SB landing on autumn (89 mL/kg SB) and winter (67 mL/kg SB), and the best content in ω-3 fatty acids was also found in autumn (257 g/kg oil). In general, FPH and oil from gurnard residues were excellent in productive, compositional and nutritional terms, indicating their valuable interest as potential food and nutraceutical ingredient. Highlights: Added-value products were obtained by Alcalase hydrolysis of gurnard wastes. ω-3 oils and fish protein hydrolysates (FPHs) were concomitantly produced. Production and chemical properties of FPHs were in general independent of seasons. Oils from autumn and spring showed highest ω-3.